Estudio y diseño del sistema de alcantarillado sanitario y pluvial, agua potable de la lotización Las Orquídeas del cantón Santa Rosa - provincia de El Oro. - Capa Balladares, Simón Abraham (2014)
The current population in its desire to settle in one place, looking for places to live where there are no basic services , causing their living conditions is not the most optimal ; often they live in unhealthy places and exposed to countless diseases. Seeking to solve in part these social problems, an environmental analysis was conducted to determine the places that do not have these services and establish a study of sewage, sanitary and storm , design of drinking water to help improve the quality of life of the inhabitants orchids of lot of the city of Santa Rosa.